2008
DOI: 10.1373/clinchem.2008.105189
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Kallikrein-Related Peptidases (KLKs) as Cancer Biomarkers

Abstract: Background: The human kallikrein-related peptidase (KLK) family consists of 15 highly conserved serine proteases, which are encoded by the largest uninterrupted cluster of protease genes in the human genome. To date, several members of the family have been reported as potential cancer biomarkers. Although primarily known for their biomarker value in prostate, ovarian, and breast cancers, more recent data suggest analogous roles of KLKs in several other cancers, including gastrointestinal, head and neck, lung, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 39 publications
1
73
0
4
Order By: Relevance
“…Furthermore, dysregulated kallikreinrelated peptidase gene and protein expression has been implicated in cancer (10). In particular, numerous clinical studies have linked the differential expression signatures of KLK genes and proteins to their potential roles as cancer biomarkers (11). Kallikrein-related peptidases may be involved in different stages of cancer growth and progression including cell growth and survival, differentiation, remodeling of extracellular matrix, invasion, angiogenesis, and metastasis (4,10,12).…”
mentioning
confidence: 99%
“…Furthermore, dysregulated kallikreinrelated peptidase gene and protein expression has been implicated in cancer (10). In particular, numerous clinical studies have linked the differential expression signatures of KLK genes and proteins to their potential roles as cancer biomarkers (11). Kallikrein-related peptidases may be involved in different stages of cancer growth and progression including cell growth and survival, differentiation, remodeling of extracellular matrix, invasion, angiogenesis, and metastasis (4,10,12).…”
mentioning
confidence: 99%
“…The association of kallikrein-related peptidases (KLKs) and cancer is well documented in the literature and many KLKs have been shown to be dysregulated in different malignancies (Emami and Diamandis, 2008). Several independent reports have shown that many KLKs are dysregulated in ovarian cancer.…”
mentioning
confidence: 99%
“…Although testicular cancer presents a rising incidence among younger men, the low mortality rates of the disease have not yet encouraged the study of KLK expression. Therefore, a significant prognostic impact has been revealed only for KLK5 expression, as its correlation with lower stages of the disease indicates a more propitious outcome for these patients (Emami and Diamandis, 2008). In the case of renal cell carcinoma, the fact that a large number of patients suffer from advanced stages of the disease, at the time of diagnosis, indicates that prognostic biomarkers capable of clarifying patients' outcome should be the most essential clinical aim.…”
Section: Testicular and Renal Cancersmentioning
confidence: 99%
“…Expression analysis of KLK7 in intracranial tumors negatively correlates the mRNA expression levels of this gene with OS probability of patients, whereas KLK7 synthesis has been associated with an enhanced invasive potential of cancer cells, clarifying the unfavorable impact of KLK7 for these tumors (Emami and Diamandis, 2008).…”
Section: Other Types Of Cancermentioning
confidence: 99%
See 1 more Smart Citation